Amérique septentrionale [sheet 1] - Anville, Jean Baptiste Bourguignon d’, 1697-1782 (Cartographer); Haye, G. de la (Engraver)
This is sheet 1 of a 1746 map of North America showing settlements, waterways and islands. "Publiée sous les auspices de Monseigneur le Duc d'Orleans, Prémier Prince du Sang, par le Sr. d'Anville" Scale approximately 1:6,250,000. Relief shown pictorially. From author's Atlas général. [1727-1780]. Shows settlements, waterways and islands. Includes inset of the Hudson Bay-Labrador region. In French. [Gravé par Guill. Delahaye] Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .